2009
DOI: 10.1002/cmdc.200900290
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation of 1,1‐Diarylethylenes as a Novel Class of Antimitotic Agents

Abstract: The cytotoxic activities of 23 new isocombretastatin A derivatives with modifications on the B-ring were investigated. Several compounds exhibited excellent antiproliferative activity at nanomolar concentrations against a panel of human cancer cell lines. Compounds isoFCA-4 (2 e), isoCA-4 (2 k) and isoNH(2)CA-4 (2 s) were the most cytotoxic, and strongly inhibited tubulin polymerization with IC(50) values of 4, 2 and 1.5 microM, respectively. These derivatives were found to be 10-fold more active than phenstat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…Thus, we have demonstrated that it is possible to replacet he Z-1,2-diarylethylene scaffold of CA-4 with 1,1-diarylethylene to give isoCA-4, as tructural isomer of CA-4, with biological activities similar to those of the natural product. [18,19,22] We next showedt hat it is possible to reduce the double bond of isoCA4t of urnish (AE)-isoerianin 2a, [20] which also displayed excellent anticancer activities similartothose of natural erianin. [23] We recently prepared azaisoerianin derivatives 3 and were pleased to observe that such compounds are as potent as their C-congeners.…”
Section: Combretastatinmentioning
confidence: 99%
“…Thus, we have demonstrated that it is possible to replacet he Z-1,2-diarylethylene scaffold of CA-4 with 1,1-diarylethylene to give isoCA-4, as tructural isomer of CA-4, with biological activities similar to those of the natural product. [18,19,22] We next showedt hat it is possible to reduce the double bond of isoCA4t of urnish (AE)-isoerianin 2a, [20] which also displayed excellent anticancer activities similartothose of natural erianin. [23] We recently prepared azaisoerianin derivatives 3 and were pleased to observe that such compounds are as potent as their C-congeners.…”
Section: Combretastatinmentioning
confidence: 99%
“…Chemical shift values (d) are given in ppm relative to the residual solvent peak (CHCl 3 ) as the internal reference, and coupling constants (J) are given in Hertz. All 13 C NMR spectra were recorded with complete proton decoupling. Peak assignment was unambiguously performed using HMQC, HMBC, and NOESY techniques.…”
Section: Chemistrymentioning
confidence: 99%
“…[12] Many linkers that constrain the two phenyl rings to a similar cis-restricted conformation have been reported to increase the activity and stability of the designed compounds relative to CA4. This approach was mainly achieved by replacement of the double bond with other rigid linkers [13] or different cyclic moieties, [14] or by introducing another ring. [15] These considerations led us to design a new series of conformationally restricted CA4 analogues by inserting an additional ring between the cis-olefinic bond and one of the aromatic moieties of the CA4 structure.…”
Section: Introductionmentioning
confidence: 99%
“…By structural modifications on the B ring, we have also identified other promising antiproliferative agents such as isoFCA-4 and iso-NH 2 CA-4 ( Fig. 1) [37]. In addition, these apoptosis inductors substances were found to inhibit microtubules formation and to induce cell cycle arrest in G2/M phase.…”
Section: Introductionmentioning
confidence: 97%